PENGARUH UMUR PERUSAHAAN, OPINI AUDIT, REPUTASI KAP, DAN KOMPLEKSITAS OPERASI TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BEI 2021-2023) - Sari, Dewi Permata; Indrawati, Novita; Afifah, Ulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study was conducted to determine the effect of company age, audit opinion, reputation ofpublic accounting firms, and complexity of operations on the timeliness of financial reportsubmission in energy sector companies listed on the Indonesia Stock Exchange. This study applieda quantitative study using secondary data. The population in this study were all energy companieslisted on the Indonesia Stock Exchange (IDX) in the 2021-2023 period. The research sample wasselected using the purposive sampling method, so that the sample obtained was 55 samples. Datawere obtained from annual financial reports obtained through the official website of the IndonesiaStock Exchange and other related websites. The data analysis technique used in this study wasdescriptive statistics with the help of SPSS (Statistic Package for Social Science) software version25. The results of the study showed that the independent variables, namely company age,reputation of public accounting firms, and complexity of operations had no significant effect onthe timeliness of financial report submission. Meanwhile, the audit opinion variable showed asignificant effect on the timeliness of financial report submission.Keywords: Company Age, Audit Opinion, Public Accounting Firm Reputation, OperationalComplexity, and Timeliness of Financial Report Submission